2017
DOI: 10.1080/13685538.2017.1401993
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 and testosterone levels in men with metabolic syndrome

Abstract: In this study, higher IL-18 levels were found in the presence of MS compared to healthy men, but they did not differ between men having MS with or without LOH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…In our study, we draw a conclusion that both obese men and metabolic unhealthy men had a higher risk of developing low serum TT levels than normal weight and metabolic healthy individuals, which is consistent with the results in previous study [8][9][10][11]13]. It demonstrated that serum TT levels in male population were associated with BMI and different components of metabolic syndrome.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, we draw a conclusion that both obese men and metabolic unhealthy men had a higher risk of developing low serum TT levels than normal weight and metabolic healthy individuals, which is consistent with the results in previous study [8][9][10][11]13]. It demonstrated that serum TT levels in male population were associated with BMI and different components of metabolic syndrome.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of metabolic syndrome ranges from 10 to 34 percent according to different de nitions or populations [7]. Several studies have pointed that metabolic syndrome can be regarded as an independent association with low levels of total testosterone in male population [8][9][10][11]. And low levels TT and SHBG can be considered as independent risk factors for metabolic syndrome [12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Like other pro-inflammatory cytokines (such as IL-1β, TNFα, interleukin 6 (IL-6) ( 13 , 14 , 15 , 16 ) and high-sensitivity C-reactive protein (hs-CRP) ( 17 )), elevated IL-18 level is a characteristic of obesity and the metabolic syndrome ( 18 , 19 , 20 ), and is reduced by weight loss ( 19 , 21 ). The presence of the metabolic syndrome is associated with even higher IL-18 concentration than obesity alone, as has been shown for IL-6, TNFα and CRP ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we draw a conclusion that both overweight/obese men and metabolic unhealthy men had a higher risk of developing low serum TT levels than normal weight and metabolic healthy individuals, which is consistent with the results in previous studies. [8][9][10][11]13 It demonstrated that serum TT levels in the male population were associated with BMI and different components of metabolic syndrome. A Korean study has shown that serum TT levels were negatively associated with BMI, WC, FPG, TG, and blood pressure, and positively associated with HDL-L levels.…”
Section: Discussionmentioning
confidence: 99%
“…7 Several studies have pointed that metabolic syndrome can be regarded as an independent association with low levels of total testosterone in males. [8][9][10][11] And low levels of TT and SHBG can be considered as independent risk factors for metabolic syndrome. 12,13 However, the relationship of TT with metabolic syndrome remains inconsistent.…”
Section: Introductionmentioning
confidence: 99%